Understanding the importance of service in the beach volleyball game - Gabriel Alexandru PETROVICI (Editura Universităţii din Oradea, 2021)
Beach volleyball is a practical sports game practiced both by the high-performance athlete and the great mass of lovers of movement, for recreational purposes, of lousier. In recent years, an increasing number of participants and tournaments have led to several studies on beach volleyball. Beach volleyball is divided into two phases: defense and counterattack. The sequence of beach volleyball actions is service, taking over, lifting, attacking, blocking, and diving. The defense phase includes: taking over, lifting, and attacking. Counterattack includes: blocking, defending, lifting, and attacking. This research tries to identify beach volleyball's fundamental characteristics and highlights the main ideas regarding this critical skill in beach volleyball. This technical procedure was and will be one of the most important in the volleyball game - both beach and indoor. Beach volleyball service is a specific motor skill commonly described as the first element of defense, essential to prevent a team from getting the side-out.